Technology uses and student achievement: A longitudinal study - Lei, Jing; Zhao, Yong (Computers and education, 2007)
Based on data collected from a middle school, this study investigates how the quantity and quality of technology use affect student learning outcomes. Specifically, this study examines how technologies are used by students, what technology uses are popular among students, and what technology uses are effective for increasing student academic achievement. Results suggest that the quantity of technology use alone is not critical to student learning. “How much” matters when “how” is identified. Moreover, when the quality of technology use is not ensured, more time on computers may cause more harm than benefit. With students’ change in GPA as an indicator, technology uses that had positive impact on students were those related to specific subject areas and focused on student construction. In addition, analysis of the frequency of technology uses found that, in general, technology uses that had positive impact were not popular; on the contrary, some of these technology uses were the least frequently used. Implications for practice and future research are discussed in this paper.